Cyclometalation and coupling of a rigid 4, 5-bis(imino)acridanide pincer ligand on yttrium1. Issue 25 (7th July 2015) - Wong, Edwin W. Y.; Emslie, David J. H.
<x xml:space="preserve">Abstract</x> The synthesis and reactivity of a rigid new pincer pro-ligand, 4, 5-bis{(diphenylmethylene)amino}-2, 7, 9, 9-tetramethylacridan, H[AIm2], with [Y(CH2SiMe3)3(THF)2] is reported, and the donor–π-acceptor dye-like properties of the resulting yttrium complexes, H[AIm2] and Lix[AIm2]x are described.